1991
DOI: 10.1002/1097-0142(19911215)68:12<2561::aid-cncr2820681205>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion gallium nitrate for patients with advanced refractory urothelial tract tumors

Abstract: A Phase I‐II trial of gallium nitrate was conducted in 40 patients with bidimensionally measurable urothelial tract tumors who had failed to respond to combination chemotherapy with methotrexate, vinblastine, doxorubicin, and cisplatin. Partial responses were observed in 4 of 23 patients (17.4%) who received 350 mg/m2/d or more for 5 days by continuous intravenous infusion. In two additional patients who received 350 mg/m2/d or more, a minor response and a mixed response were observed. The median duration of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…There are currently three main agents in clinical studies. The first is based on gallium nitrate, which interferes with the release of iron from endocytic vesicles, the second is iron chelation, and the third treatment is based on the use of mAbs or small molecules against transferrin or the TfR (25)(26)(27)(28)(29)(30)(31)(32)(33). In this study, we showed that two different anti-TfR mAbs A27.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently three main agents in clinical studies. The first is based on gallium nitrate, which interferes with the release of iron from endocytic vesicles, the second is iron chelation, and the third treatment is based on the use of mAbs or small molecules against transferrin or the TfR (25)(26)(27)(28)(29)(30)(31)(32)(33). In this study, we showed that two different anti-TfR mAbs A27.…”
Section: Discussionmentioning
confidence: 99%
“…Gallium (Ga) is group IIIa metal salt with significant activity against bladder cancer and lymphoma (Warrell et al, 1983;Chitambar and Seligman, 1986;Chitambar et al, 1988;Crawford et al, 1991;Seidman et al, 1991;Seligman and Crawford, 1991). Moreover, gallium, as its radioisotope 67 Ga, is widely used clinically for the effective radio imaging of tumors (Chitambar, 2004).…”
mentioning
confidence: 84%
“…15 Clinical trials have demonstrated activity against some malignancies, including epithelial ovarian carcinoma, non-squamous cell carcinoma of the cervix, bladder cancer 16,17 and non-Hodgkin's lymphoma. Other clinical trials under way include studies of sarcoidosis and rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%